Development of sustainable rural tourism at Sungai Sedim Amenity Forest, Kedah, Malaysia from a tourism stakeholders’ perspective - Che Aziz, Roslizawati (2016)
The main focus of the study is to explore the development of sustainable rural tourism at Sungai Sedim Amenity Forest (SSAF), one of the most popular destinations in Malaysia. The forest is located in the north of Peninsular Malaysia, within Sedim’s area and near Karangan, 30km from Kulim’s town.The World’s Longest Canopy Walk, the 925m long and 50m high Tree Top Walk (TTW), is among the best attractions at SSAF and offers great aerial views of the natural forest. The study is concerned with the past and current situations of tourism development at SSAF from a different perspective of stakeholders; local communities, authorities, operators as well as visitors. The data was collected from 59 participants who directly and indirectly involved with tourism activities at SSAF. The information was derived from two focus group discussions and semi-structured interviewed. Appreciative Inquiry (AI) approach was applied as a new tool or approach for conducting the research while ATLAS.ti software was used as a tool for data interpretation and analysis.The findings show that there are four strengths of SSAF that need to be highlighted, which are nature resources, eco-tourism activities, TTW and historical/ cultural elements. In addition to that, the study also shows that there are few potentials of SSAF from the perspective of tourism stakeholders; niche products, home-stay, cultural and architectural value, entrepreneurship development, education and research center as well as infrastructures and facilities development. The social, economic and environment elements have been identified as the impact factors that contributed to the development of tourism activities at SSAF. In support of this finding, the results also showed that there are broadly similar views among the participants towards tourism development and their engagement in this industry, thus will put greater emphasis to see more tourism activities, and products will be developed at SSAF. The results also clearly indicate the significant contributions of rural tourism development and there are obvious direct and indirect potentials and contributions of rural tourism that have resulted from an increase in tourism development at SSAF. The partnership between the government, tourism operators, and the local communities in forest management plays an important part for SSAF, especially for the purpose of preserving and conserving theforest and nature. The study also strives to contribute to this growing area of research by bringing wider benefits of rural development to SSAF based on The 10th Malaysian Plan (RMK-10) with a holistic and coordinated approach that boosts the tourism industry. The implication of this is that it is a significant stress on economic, environmental, and socio-cultural roles that affects all the stakeholders. Hence, this study also provides much scope to expand the literature by considering methods to apply the Appreciative Inquiry approach to rural tourism development.